'If you didn't laugh, you'd cry': Emotional labour, reflexivity and ethics-as-practice in a qualitative fieldwork context. Issue 2 (June 2020) - McGowan, William
This article takes Guillemin and Gillam's distinction between 'procedural ethics' and 'ethics in practice' as a point of departure and return for reflecting critically on a recently completed doctoral research project about political violence and terrorism. It provides an overview of the study before offering some instructive vignettes to show how ethical decision-making processes engaged with 'in the field' were an extension of more everyday and mundane reasoning than we may typically associate with such quintessentially 'sensitive research'. As the final section of this article argues, it is this everyday and mundane quality to ethical reasoning which is sometimes obscured in formal accounts of 'reflexivity'. It is hoped that this article is useful for scholars interested in the ethics and emotional practices of qualitative inquiry, as well as those researching serious violence and bereavement.